Pengembangan Alat Peraga IPA dari Barang Bekas Untuk Meningkatkan Minat dan Motivasi Belajar Siswa SMP - Pratiwi, Zuliana Eka; Pramesti, Salsabila Aprillyanti; Rosidah, (Faculty of Mathematics and Natural Sciences, Universitas Negeri Surabaya, 2022)
There are still a few simple teaching aids available for studying Pascal's law and hydrostatic pressure. The development of teaching aids in the form of a “mini dispenser” is intended to help students understand more in real terms and details related to Pascal's law and hydrostatic pressure. In addition,